Development of a functional bioassay to study the mechanism of action of a novel phenylethylamine alkaloid, schwarzinicine A - Loong, Bi Juin (2016)
Hypertension is the most prevalent risk factor leading to cardiovascular diseases. Resistant or uncontrolled hypertension urges the discovery and development of new drug candidates in treating this health concern. Plant-derived biological active compounds are always the alternative drug candidates for many diseases. This study aims to investigate and characterise the vascular effects of a novel plant phenylethylamine alkaloid, schwarzinicine A from Ficus schwarzii. A functional bioassay methodology using four different rat tissues such as trachea, bronchus, aorta and bladder was first optimised at fresh and stored conditions. The functionality of this optimised methodology was proven effective in testing ten different plant alkaloids on rat aorta. This was followed by preliminary testing of schwarzinicine A on four different rat tissues such as trachea, bronchus, aorta and bladder and the results depicted that schwarzinicine A exhibited the highest relaxation efficacy in rat aorta among all tested tissues. The bladder response to schwarzinicine A was inconclusive due to the occurrence of spontaneous contractile response in bladder. Hence, rat aorta was the best candidate for further investigation of schwarzinicine A effect, whether its induced relaxant effect in rat aortic rings was influenced by endothelium and nitric oxide (NO), or was mediated by alpha- and beta-adrenergic receptors, potassium channels, cGMP/cAMP, and calcium channels. The findings showed that the aortic relaxation by schwarzinicine A was not affected by all above-mentioned modulators, with exception that it inhibited calcium channels as suggested from the reduced contraction responses of three tested contractile agents including phenylephrine (alpha-adrenergic receptor agonist), 5-hydroxytryptamine (non-selective serotonin receptor agonist) and potassium chloride (membrane depolarising agent), as well as the contractions by calcium chloride in calcium-free Krebs solution, in the prior treatments with schwarzinicine A. This hypothesis was elucidated in the mechanistic studies using porcine coronary arteries (PCA) and rat dorsal root ganglion (DRG) cells. In porcine coronary arteries, schwarzinicine A also caused the similar relaxant effect in response to U46619 pre-contraction and also the reduced contractions to calcium chloride in calcium-free experiments, as compared to those observed in rat aortic rings. Cell-based calcium imaging assay using rat DRG cells was to further elucidate the inhibitory role of schwarzinicine A in calcium channels. Schwarzinicine A was revealed to inhibit the calcium entry via dominant voltage-gated calcium channel opening by KCl. All the gathered findings from rat aorta, PCA and rat DRG cells concluded that schwarzincine A exhibited an inhibitory role on calcium channels.